Macro factors and the Brazilian yield curve with no arbitrage models - Marcos S. Matsumura; Ajax Reynaldo Bello Moreira (Institute for Applied Economic Research (ipea), 2015)
We use no arbitrage models with macro variables to study the interaction between the macroeconomy and the yield curve. This interaction is a key element for monetary policy and for forecasting. The model was used to analyze the Brazilian domestic financial market using a daily dataset and two versions of the model, one in continuous-time and estimated by maximum likelihood, and the other in discretetime and estimated by Monte Carlo Markov Chain (MCMC). Our objective is threefold: 1) To analyze the determinants of the Brazilian domestic term structure considering nominal shocks; 2) To compare the results of the discrete and the continuous time versions considering adherence, forecasting performance and monetary policy analysis; and 3) To evaluate the effect of restrictions on the transition and pricing equations over the model properties. Our main results are: 1) results from continuous and discrete versions are qualitatively and in most cases quantitatively equivalent; 2) Monetary Authorities are conservative in Brazil, smoothing short rate fluctuations; 3) inflation shock, or slope shock, depending on the model selected, are the main sources of long run fluctuations of nominal variables; and finally, 4) no arbitrage models showed lower forecasting performance than an unrestricted factor model.
Keywords: C13; E43; E52; G12; 330